2016
DOI: 10.17645/si.v4i3.546
|View full text |Cite
|
Sign up to set email alerts
|

Framing Social Inclusion as a Benchmark for Cycling-Inclusive Transport Policy in Kisumu, Kenya

Abstract: Cycling in many cities of the Global South faces unending exclusion from street spaces despite the on-going transport policy reforms. This exclusion worsens the marginalisation of the poor majority who use this mode. In this paper, we formulate social inclusion as a policy tool for reconciling transport policy to the cycling needs of Kisumu, Kenya. We draw from social quality theory and Lefebvre's right to the city concept to assemble the ideals of social inclusion. These ideals form the benchmark for a qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“…Just like in most of the developing countries, a reliable means of transport is considered to be one of the core factors in economic development in Kenya. According to Alando and Scheiner [62] cycling in most cities in African countries including Kenya faces unending exclusion, especially from Despite their cultural background, women in central Uganda, especially Kampala, Wakiso and Entebbe, cycle but at a lower level [60]. For example, New Vision [60] reported that one of the female lecturers at Makerere University has inspired most women to cycle in one way or another.…”
Section: Case Of Kenyamentioning
confidence: 99%
See 2 more Smart Citations
“…Just like in most of the developing countries, a reliable means of transport is considered to be one of the core factors in economic development in Kenya. According to Alando and Scheiner [62] cycling in most cities in African countries including Kenya faces unending exclusion, especially from Despite their cultural background, women in central Uganda, especially Kampala, Wakiso and Entebbe, cycle but at a lower level [60]. For example, New Vision [60] reported that one of the female lecturers at Makerere University has inspired most women to cycle in one way or another.…”
Section: Case Of Kenyamentioning
confidence: 99%
“…Just like in most of the developing countries, a reliable means of transport is considered to be one of the core factors in economic development in Kenya. According to Alando and Scheiner [62] cycling in most cities in African countries including Kenya faces unending exclusion, especially from the street spaces. Much as cycling is one of the cheapest transport means in East African countries, there is still limited infrastructure that supports cycling in the country.…”
Section: Case Of Kenyamentioning
confidence: 99%
See 1 more Smart Citation
“…While the majority have a European focus, with four papers addressing transport and social inclusion in UK (Clark & Curl, 2016;Marshall et al, 2016;Pooley, 2016;Velho, Holloway, Symonds, & Balmer, 2016), one in Sweden (Lättman, Friman, & Olsson, 2016) and one in France (Purwanto, 2016), three explore different elements of the African (Alando & Scheiner, 2016;Kett & Deluca, 2016) and Asian (Thynell, 2016) contexts. From a methodological perspective, the papers present a variety of approaches (qualitative, quantitative, mixed methods and a computer software simulation) drawn from a wide range of disciplinary areas, including sociology, history, gender and development studies, economics, science and technology studies, accessibility planning, engineering and transport studies.…”
Section: Overview Of the Papers Included In This Themed Issuementioning
confidence: 99%
“…Both of these papers are based on research studies conducted in sub-Saharan Africa, where non-motorised transport is prevalent and absolute poverty is widespread. Alando and Scheiner (2016) report that, in these countries, the most vulnerable women, children, older and disabled people are often prevented from making journeys because of poor road conditions, unaffordability, lack of private transport, and poor and/or unreliable public transport. This is a major cause of social exclusion.…”
Section: Overview Of the Papers Included In This Themed Issuementioning
confidence: 99%